Rancang Bangun Virtual Reality Tour Untuk Media Promosi Tempat Hangout Menggunakan Metode Multimedia Development Life Cycle - Nurhaqiqi, Lisda; Julianto, Indri Tri (Institut Teknologi Garut, 2025)
The culinary and tourism industry in Garut Regency is growing rapidly with the emergence of various cafes, restaurants, and tourist attractions that target visitors from various groups. Currently, marketing strategies are still dominated by conventional media such as images, videos, and text, which are less interactive and have not utilized digital technology optimally. Therefore, this research aims to design and build a Virtual Reality Tour Website as an innovative solution in the promotion of Hangout places in Garut. This website is designed to provide an interactive and immersive experience, allowing users to feel as if they are directly at the tourist attraction. The method used is the Multimedia Development Life Cycle (MDLC), which includes the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Website development was carried out using 3D Vista software, with Alpha and Beta testing involving 20 respondents from five tourist attractions in Garut. The test results showed a usability testing value of 4.66, indicating a very good assessment. This website provides features such as tourist information, facilities, rides, galleries, culinary, location maps, Virtual Reality Tour, automatic chat, and profile videos. With the application of Virtual Reality technology, it is expected to increase tourist attraction and popularize Hangout places in Garut at the national and international levels.